Representasi Kritik Sosial dalam Lirik Lagu “Peradaban” Band .Feast: Analisis Wacana Kritis Norman Fairclough - Ifra Imaniar Marasabessy; Antasari Bandjar; Vransisca Kissya (GLOBAL SCIENTS PUBLISHER, 2026)
This study analyzes how Peradaban, a song by . Feast, depicts social criticism using Norman Fairclough's Critical Discourse Analysis framework. It aims to examine the meanings generated by the lyrics in contemporary Indonesian society that relate to religious intolerance, moral policing, identity suppression, and inclusive nationalism. The study employs a qualitative descriptive methodology to analyze three areas: textual, discursive, and social conduct. The normalization of violence and symbolic oppression against minority groups is emphasized textually by the use of repetition, metaphor, and aggressive language. The song's discursive use as a counter-discourse against radicalism and exclusive religious interpretations is supported by the band's critical identity and online distribution. On a social practice level, the song emphasizes power imbalances between majority and minority populations while also promoting an emancipatory notion of inclusive nationalism. According to study, popular music in modern Indonesia functions as a discursive practice that mediates social values and fosters critical awareness.